Essays in development economics - Boudot-Reddy, Camille (The University of Edinburgh, 2022)
The thesis consists of three independent chapters, each of which investigates a distinct research question pertinent to development economics. The first chapter explores the influence of marketing pressure on targeted health product purchase and usage. The second chapter evaluates the impact of improving access to rural banking infrastructure on agricultural production choices. The third chapter assesses the effect of irrigation on the structural transformation of the rural economy. Chapter 1 -- Improving the Adoption of Household Health Products: A Sales Experiment with Chlorine Tablets. We test a door-to door marketing intervention aimed to increase use of a targeted health product among poor households. Specifically, we examine three treatments in which this good - chlorine tablets for drinking water purification - is: (1) sold alone, (2) sold alongside a familiar and cheaper side good that is priced at its retail value, and (3) sold alongside the same side good that is priced on a promotional offer. The side good when sold at retail price is intended to be an "opt-out" good to reduce the marketing pressure, which should in turn reduce the amount of products sold that go unused. When the side good is sold on promotion, however, we hypothesize that it reintroduces marketing pressure due to the "gift" aspect of the promotion. Consistent with this hypothesis, we find that chlorine use is nearly double in the second condition compared to the other two conditions. Our results suggest that household valuation of a new product is shaped by both the presence and the price of a side good due to marketing pressure. Chapter 2 -- The Production Effects of New Banking Infrastructure: Evidence from Rural India. We study the production effects of one of the largest bank branch expansion programs in history, implemented by the government of India during the 1980s. Combining policy-driven variation in branch expansion with newly-digitized data on bank lending and crop prices at the district-year level, we find that a 1% growth in rural branches increased aggregate yields by 0.3% over a three year period. This effect is largely driven by a higher incidence of cropping during the dry winter season. Banks also attenuate the effect of lagged rainfall shocks on output, via changes in the use of costly irrigation resources. Chapter 3 -- Watering the Seeds of the Rural Economy: Impact of Tube-Well Irrigation in India. We study the average village level effects of access to groundwater for irrigation on the structural transformation of the rural economy. Using newly assembled data on irrigation practices, we exploit an absolute technological constraint imposed by the laws of physics on the operational capacity of pumps with depth of the water table in a fuzzy regression kink design. Our results show that increased access to irrigation, measured as an additional standard deviation unit ( approximately 103 litres/ha/day) of groundwater, significantly boosts agricultural land production. Farmers respond to an increase in groundwater for irrigation by expanding their cultivated land area by over 12%, and shifting away from drought tolerant crops. This substantial shift in agricultural production translates into significant consumption gains, including a 4% drop in the share of the village population living below the poverty line. Within the agricultural sector, we find that approximately 6 to 10% of cultivators and manual labourers respectively shift from part-time to full-time employment. However, we find no evidence of labour re-allocation between different sectors of the local village economy.